2013
DOI: 10.2147/rru.s39288
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the phytotherapeutic drug Canephron® N in prevention and treatment of urogenital and gestational disease: review of clinical experience in Eastern Europe and Central Asia

Abstract: This review evaluates 17 clinical studies from 18 selected publications concerning the safety, tolerability, and additional effects of the phytotherapeutic drug, Canephron® N (CAN, containing the medicinal plants, Centaurium erythraea, Levisticum officinale, and Rosmarinus officinalis) as standard therapy in various clinical settings. Its role in the prophylaxis and treatment of urinary tract infections in adults and in children, therapy and prophylaxis in adult patients with renal stones, treatment and preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 6 publications
0
23
0
6
Order By: Relevance
“…This medical drug consists of a fixed combination of herbal components standardized by the composition of key active ingredients of herbs: centaury, lovage root and medical rosemary leaves. Such combined composition provides a complex effect on the kidneys and the urinary tracts that is expressed in a moderate diuretic [11,17] and spasmolytic action [18] associated with the ability of the study drug to improve urodynamics and contribute to faster elimination of calculi [19,20]. During this study, more rapid elimination of calculi fragments from the urinary tracts was also observed.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This medical drug consists of a fixed combination of herbal components standardized by the composition of key active ingredients of herbs: centaury, lovage root and medical rosemary leaves. Such combined composition provides a complex effect on the kidneys and the urinary tracts that is expressed in a moderate diuretic [11,17] and spasmolytic action [18] associated with the ability of the study drug to improve urodynamics and contribute to faster elimination of calculi [19,20]. During this study, more rapid elimination of calculi fragments from the urinary tracts was also observed.…”
Section: Discussionmentioning
confidence: 85%
“…Also, due to these properties, there were fewer cases (by 46.5 %) of lumbar pain or abdominal discomfort during elimination of disintegrated stone fragments in the treatment group. Anti-inflammatory action of herbal components in Canephron N [11] is of great importance, which contributes to rapid regression of consequences of the urinary tract mucosa injury and eradication of leukocyturia. This is supported by data of our study when we observed that the frequency of leukocyturia in the treatment group was 56.5 % less than in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized preparations like Canephron N containing centaury, lovage, and rosemary exhibit not only anti-oxidative and nephroprotective but also diuretic and anti-inflammatory effects. This unique combination of antiurolithiatic effects is very promising 32, 33 . However, this has to be validated by randomized studies.…”
Section: Understanding Urolithiasismentioning
confidence: 99%
“…A number of potentially useful plants have been identified in this way, which have been incorporated into commercial products (Albrecht et al . ; Naber ).…”
Section: Introductionmentioning
confidence: 99%